Il Sessantotto. La battaglia contro le istituzioni e la psichiatria “etico-pedagogica” di Franco Basaglia - Lentini, Stefano (Studi sulla Formazione/Open Journal of Education, 2019)
1968 presents itself as a unique interweaving of student protest, of redefining family and generational relations, of gender relations. That revolutionary experience in other countries is exhausted during the “red biennium” (1968-1969); in Italy it continued over the “movement season”, with a critical reflection that, starting from the family, put the “institutions” into question. In this climate of renewal, Franco Basaglia, from 1961 director of the psychiatric hospital of Gorizia (until 1969), started a new psychiatric, psychological, pedagogical and anthropological cultural tradition in Italy, which in a few years opened the way to a psychiatry that we could call “ethical-pedagogical”.